Mutations in the small subunit of ribulose-1,5-bisphosphate carboxylase/ oxygenase increase the formation of the misfire product xylulose-1,5-bisphosphate. - Flachmann, R (1997)
The small subunit (S) increases the catalytic efficiency of ribulose-1,5-bisphosphate carboxylase/oxygenase (EC 4.1.1.39) by stabilizing the active sites generated by four large subunit (L) dimers. This stabilization appears to be due to an influence of S on the reaction intermediate 2,3-enediol, which is formed after the abstraction of a proton from the substrate ribulose-1,5-bisphosphate. We tested the functional significance of residues that are conserved among most species in the carboxy-terminal part of S and analyzed their influence on the kinetic parameters of Synechococcus holoenzymes. The replacements in S (F92S, Q99G, and P108L) resulted in catalytic activities ranging from 95 to 43% of wild type. The specificity factors for the three mutant enzymes were little affected (90-96% of wild type), but Km(CO2) values increased 0.5- to 2-fold. Mutant enzymes with replacements Q99G and P108L showed increased mis-protonation, relative to carboxylation, of the 2,3-enediol intermediate, forming 2 to 3 times more xylulose-1,5-bisphosphate per ribulose-1,5-bisphosphate utilized than wild-type or F92S enzymes. The results suggest that specific alterations of the L/S interfaces and of the hydrophobic core of S are transmitted to the active site by long-range interactions. S interactions with L may restrict the flexibility of active-site residues in L.